Deck the halls [videorecording (DVD)] - Whitesell, John; DeVito, Danny; Broderick, Matthew, 1962-; Davis, Kristin, 1966- (20th Century Fox Home Entertainment, 2007)
Two neighbors in a small New England town go to war when one of them decides to decorate his house with a so many Christmas lights that they are visible from space. The neighborhood is turned upside down as the families try to discover the true meaning of Christmas.